Agricultural Policy in Kenya Applications of the Policy Analysis Matrix - Monke, Eric A.; Argwings-Kodhek, Gem; Avillez, Francisco; Pagiola, Stefano; Sellen, Daniel; Winter-Nelson, Alex (Cornell University Press, 2019)
Kenya is desperately seeking opportunities for higher incomes and productive employment. Its population is among the fastest growing in the world, and the key to economic growth lies in the productivity of its farmers. The authors spent two years doing field work in Kenya and collecting data. Their book provides a microeconomic perspective on opportunities for income and employment growth, especially for small farms. The authors emphasize the impact of government policies on production incentives to show how policy changes might lead to greater incomes. Kenyan agricultural policy targets three kinds of changes in farming practices—increasing the area devoted to cash crop production, improving the efficiency of processing and transportation so that farm-gate prices will rise, and increasing the use of purchased inputs, such as fertilizer
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Sep 2019)
Keywords: Agriculture; Nature Guides & Natural History; POLITICAL SCIENCE / Public Policy / Agriculture & Food Policy (see also SOCIAL SCIENCE / Agriculture & Food)